Analisis Program Bilingual dalam Perkembangan Bahasa Inggris KG 1 di Kiddos Preschool - Ni Nyoman Pande Pemi Rusma Urip; Luh Made Dwi Wedayanthi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Education in early childhood is the main foundation in individual development, especially in forming personality, social skills and cognitive abilities. One important aspect in early childhood education is the introduction of language, especially English which acts as a global lingua franca. This research analyses the effectiveness of the bilingual program in improving the English language skills of KG 1 students at Kiddos Preschool Gianyar. Bilingual programs are introduced through various methods such as educational games, songs, stories and murals that support language development in a natural and fun way. The research results show that this program has a positive impact on the development of students' vocabulary, comprehension and speaking skills. Factors such as interactive teaching methods, teacher and parent support, and the availability of adequate learning resources are the keys to the success of this program. Suggestions are given to increase the effectiveness of the program through innovative learning methods and continuous training for teachers, as well as strengthening collaboration with parents.